2007
DOI: 10.1177/1045389x06063460
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Resistant Miniature Piezoceramic Actuators

Abstract: Piezoelectric ceramics are desirable actuator materials for many biomedical applications due to their ability to generate precise, controlled motion with applied voltage. Herein, we report the fabrication of miniature piezoceramic actuators and their subsequent performance testing under high electric fields. Actuators were produced by tape casting sub-micrometer lead zirconate titanate (PZT) powder, followed by electroding, laminating, and dicing to form multilayer devices. The resulting devices consisted of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…From the results reported by Hooker et al [6] it might be expected that the life time performance of CMA's with PG01 will outperform those with PXE55 because of the smaller grain size and the smaller distribution. Another factor which is important for the life time behavior of CMA's is the poling process itself.…”
Section: Resuls and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…From the results reported by Hooker et al [6] it might be expected that the life time performance of CMA's with PG01 will outperform those with PXE55 because of the smaller grain size and the smaller distribution. Another factor which is important for the life time behavior of CMA's is the poling process itself.…”
Section: Resuls and Discussionmentioning
confidence: 96%
“…However, the coercive field does not change with particle size. Finally, Hooker et al [6] shows that a decrease of the grain size in actuators improves the fatigue resistance during continuous cyclic operation. This shows that grain size control can be used to minimize performance degradation, improve reliability and promote longterm stability.…”
Section: Introductionmentioning
confidence: 98%
“…We found that the fractional change in P r as a result of cyclic actuation was significantly smaller for samples processed at T S < 1250 °C, indicating a higher fatigue resistance in this temperature range. However, a nearly constant level of fatigue (≈50 % of P init ) is found for T S > 1250_°C (more detailed results of electrical polarization-fatigue measurements can be found elsewhere [9]). In the following, these electrical results will be explained by the observed changes in microstructure.…”
Section: Electrical Measurementsmentioning
confidence: 92%
“…The piezoelectric layers modeled in this work have a working range of -500V to 1500V. However, frequent use at these high voltage levels can lead to degradation of the piezoelectric and a reduced lifespan (Pritchard, Bowen and Lowrie, 2001;Hooker et al, 2007). Furthermore the use of drive voltages in excess of 1000V may limit application of the technology due to safety concerns or the need to rectify local power sources.…”
Section: Combined Use Of Two Piezoelectric Layersmentioning
confidence: 99%